TELEMETRI SUHU MENGGUNAKAN MODEM WIRELESS YS-1020 BERBASIS MIKROKONTROLER - , IMAM MUTTAQIN ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Telemetry is a good distance measurement system using an intermediary cable and non-cable which serves to determine the value and condition of an object. One application of this telemetry is telemonitoring. By using ATmega16 microcontroller as the control center of both the sender and the receiver, LM35 temperature sensor, RF module YS-1020, and also 16 x 2 LCD viewer. The temperature telemetry works by processing the data from the sensor LM35 output voltage which is then converted into temperature data has been programmed with a programming language CodeVision AVR. Maximum measurement distance of this tool is 110m on the condition of not blocked, and 70m in the blocked condition, according to information on the RF module datasheet YS-1020. The data is displayed on the instrument temperature data are represented by Temp1 and Temp2.